AB1421-HPR Is there any change in the demographics of ra patients candidate for bdmard therapy?. (12th June 2018) - Ban, M; Bezsila, K.; Rojkovich, B.
Abstract : Background: There ara an increasing number of data that rheumatoid arthritis (RA) patients who are candidates for bDMARD (biologic disease modifying drug) therapy have nowadays a milder disease and lower disease duration then 10 years ago. The T2T strategy aims to achieve remission. Percentage of patients achieving the treatment goals seems to be a good quality indicator. Objectives: To verify among our RA patients treated with bDMARD since 2006, whether they have lower disease activity (DAS28) and shorter disease duration and younger age nowadays then at the beginning of the biologic area. As a measure of quality: how many patients treated with bDMARD achieved remission. Methods: This is a cross sectional study. Among 455 patients RA treated with 9 different bDMARD we selected those who were treated with the most widely used at the time of the study (12.01.2017). The 103 ADA treated patients' data were collected by means of a tablets with the help of study nurses. Descriptive statistics were used for analysis of data (age and disease duration at the start of bDMARD, DAS28 at start and last visit, percentage of patients on remission). Results: 103 (incl. 15 men) biologic naive patients (age: 56±13, 1) are treated with ADA at time of the study. In 3 years cohorts (2006–2008;2009–2011, 2012–2014, 2015–2017) we found no change of age, but a slight decrease of disease duration as well as DAS28 at bDMARD initatiaton. Conclusions: In our study population on ADA treatment we did'n t find significant shift toward younger patients, but the disease duration and activity of disease at the start of the ADA treatment slightly decreased. By means of bDMARD's half of the patients achieved remission. Disclosure of Interest: None declared